Regulatory dendritic cells: there is more than just immune activation - Schmidt, Susanne V.; Nino-Castro, Andrea C.; Schultze, Joachim L. (Frontiers in Immunology, 2012)
The immune system exists in a delicate equilibrium between inflammatory responses and tolerance. This unique feature allows the immune system to recognize and respond to potential threats in a controlled but normally limited fashion thereby preventing a destructive overreaction against healthy tissues. While the adaptive immune system was the major research focus concerning activation versus tolerance in the immune system more recent findings suggest that cells of the innate immune system are important players in the decision between effective immunity and induction of tolerance or immune inhibition. Among immune cells of the innate immune system dendritic cells (DCs) have a special function linking innate immune functions with the induction of adaptive immunity. DCs are the primary professional antigen presenting cells (APCs) initiating adaptive immune responses. They belong to the hematopoietic system and arise from CD34+ stem cells in the bone marrow. Particularly in the murine system two major subgroups of DCs, namely myeloid (mDCs) and plasmacytoid DCs (pDCs) can be distinguished. DCs are important mediators of innate and adaptive immunity mostly due to their remarkable capacity to present processed antigens via major histocompatibility complexes (MHC) to T cells and B cells in secondary lymphoid organs. A large body of literature has been accumulated during the last two decades describing which role DCs play during activation of T cell responses but also during the establishment and maintenance of central tolerance (Steinman et al., 2003). While the concept of peripheral tolerance has been clearly established during the last years, the role of different sets of DCs and their particular molecular mechanisms of immune deviation has not yet fully been appreciated. In this review we summarize accumulating evidence about the role of regulatory dendritic cells in situations where the balance between tolerance and immunogenicity has been altered leading to pathologic